Study on Carbon Stock of Leasehold Forests of Katakuti VDC, Dolakha District - Lama, Tshering Dolma; Mandal, Ram Asheshwar (The Initiation, 2014)
A study was carried on ten leasehold forests of Katakuti VDC, Dolakha district to estimate the carbon stock. Random sampling was used to collect the biophysical data of trees/ poles, sapling, root and leaf litter, herb and grass. Then, the biomass was calculated using the respective equation and the calculated biomass stock was converted into carbon stock multiplying with 0.47. Similarly, the soil samples were collectewd from different depths of 0-10 cm, 10-20 cm and 20-30 cm to determine the soil organic carbon. Lastly, all analyzed data were compiled to get total carbon stocks. The result showed that the estimated total carbon stock per ha was found to be highest in Srijana leasehold forest with 125.493 t C/ha. The estimated total carbon stock of 10 leasehold forest was found to be 1439.033 tons. Here, Leasehold forests have been an emerging and successful example in conserving forests in epal. So, it is recommended to extend such studies in other parts of Nepal. DOI: http://dx.doi.org/10.3126/init.v5i0.10255 The Initiation 2013 Vol.5; 63-67